Analysis of QoS Platform Cooperation Strategies - Jochen Wulf; Felix Limbach; Rüdiger Zarnekow (International Telecommunications Society (ITS), 2010)
In this paper we present a value-oriented modeling approach fort he assessment of the QoS interconnected market. This approach is based on the economics of two-sided markets and takes cross-side market externalities between networks into account. The presented model comes along with a realistic number of players and a higher level of complexity, we are proposing the use of a bottom-up, agent-based model. The novel micro-level modelling approach enables the analysis of QoS interconnection strategies. This model can be used to analyze macro-level simulation results and derive implications for the network type specific optimal interconnection stratagies.
Keywords: 330